PENGARUH STRUKTUR MODAL, UKURAN, PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN PERTUMBUHAN SEBAGAI MODERATING - Hariyawan, Bayu Eko; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe firm value is the perceptionof investorsto the company which is often associated with stock pricein whichthe stock price can increase the firm value. The firm value is proxied by market-to-book ratio (MBR), which is the ratio between the market price per share to book value of equity per share. This researchis aimed to find out the positive influence of capital structure, firm size, profitability and company growth as the moderating variable to the firm value. The object of the research is consumers goods companies which arelisted in Indonesia Stock Exchange in2011-2015 periods.The sample collection technique has been done by using purposive sampling, i.e.by selecting sample based on considerations or certain criteria. 18 consumer goods companies have been selected as samples, so the distributionwhich has been used in this researchare 90 samples. The data analysis technique has been done by usingregression moderation analysis.The result of the research shows that capital structure, firm size, and profitability has positive influencetothe firm value. The positive influence of capital structure and profitability to the firm value which moderatecompany growth, can strengthen itscorrelation. Meanwhile, the presence of negative influence of firm size to the firm value which moderates company growth weaken the correlation.Keywords: capital structure, firm size, profitability, company growth, firm value